Sex hormone Profile in Human Immunodeficiency Virus-Infected Men and It's Correlation with CD4 Cell Counts - Aggarwal, Jyoti (Indian J Endocrinol Metab, 2018)
BACKGROUND: In human immunodeficiency virus (HIV)-infected men, hypogonadism is the most common endocrinological disorder, and most cases of hypogonadism are secondary. The aim of this study was to find out the hormonal abnormalities in HIV-infected males and it's correlation with CD4 cell counts. MATERIALS AND METHODS: One hundred HIV-infected male patients were evaluated in the Department of Medicine, Postgraduate Institute of Medical Education and Research and Dr. Ram Manohar Lohia Hospital, New Delhi, India, over a period of 12 months from September 2014 to August 2015 using history, physical examination, routine baseline investigations, and CD4 counts. Free testosterone, dehydroepiandrosterone sulfate (DHEAS), luteinizing hormone (LH), follicle-stimulating hormone (FSH), and prolactin were measured using an overnight fasting sample. Patients were divided into three groups on the basis of CD4 counts (Group A: CD4 counts ≥350/mm(3), Group B: CD4 counts between 200 and 349/mm(3), and Group C: CD4 counts <200/mm(3)). Data were analyzed using Student's t-test, ANOVA test, Chi-square test, and Pearson's test and P ≤ 0.05 was considered statistically significant. RESULTS: In 100 HIV-infected males, overall prevalence of hypogonadism was found to be 66%, and 30%–35% patients had symptoms of hypoandrogenemia. Hypogonadotropic hypogonadism was found in 42% of patients. A significant association (P = 0.027) was found between prevalence of hypogonadism and the level of immunodeficiency with an increase in the prevalence of hypogonadism as CD4 counts decreased. Lower levels of free testosterone and DHEAS were found in cases of severe immunosuppression with a statistically significant correlation with CD4 counts. Correlation of other sex hormones (LH, FSH, and prolactin) with CD4 counts not statistically significant. Mean free testosterone and FSH were found to be significantly higher in patients on antiretroviral therapy (ART) than in those not on ART (P = 0.028 and P = 0.045, respectively), but no specific ART drug or their drug combination was found to have a significant correlation with levels of any sex hormone. CONCLUSION: Hypogonadism (hypogonadotropic hypogonadism) was found to be a common endocrinological disorder in HIV-infected male population, seen more commonly in association with low CD4 counts.